CHARACTERISTICS OF CHITO OLIGOSACARIDE HYDROLYSATE FROM CRAB (Portunus Pelagic) WASTE HYDROLYZED BY CHITOSANASE - Prasetyo, Mohammad Rafi; Sarofa, Ulya; -, Rosida (Universitas Dr Soetomo, 2022)
Enzymatic hydrolysis of chitooligosaccharides can be carried out using the chitosanase enzyme. Chitosanase enzyme is a glycosyl hydrolase enzyme that catalyzes the hydrolysis of Î²- 1,4 glycosidic bonds of chitosan to produce low molecular weight chitooligosaccharides. The crab shell (Portunus pelagicus) has the potential to be used as Chito oligosaccharides because the crab shell contains 20-30% chitin. This study aims to determine the effect of chitosanase enzyme concentration and duration of hydrolysis on the characteristics of chitooligosaccharides (COS) from crab shells. This research was conducted using a factorial completely randomized design (CRD) method with two factors and two replications. The factory was enzyme concentration (0.5%, 1%, and 1.5%), factor II was hydrolysis time (3 hours, 4 h, ours and 5 hours). The data were obtained using ANOVA if there was a significant difference, followed by Duncan's Test (DMRT). The results showed that the enzyme concentration (1.0%) and hydrolysis time (4 hours) was the product with the best treatment with a chemical composition of 84.96% yield, 4.83 kDa molecular weight, 86.87% degree of deacetylation and FTIR test results indicate the presence of a functional group, the OH group is obtained at a wavelength of 3624.25 cm-1 and the NH group is at a wavelength of 3404.36 cm-1. Keywords: chitooligosaccharides, chitosanase, hydrolysis,